Oligometastatic cancer: stereotactic ablative radiotherapy for patients affected by isolated body metastasis. (2nd November 2017) - Lancia, Andrea; Ingrosso, Gianluca; Carosi, Alessandra; Di Murro, Luana; Giudice, Emilia; Cicchetti, Sara; Morelli, Pasquale; di Cristino, Daniela; Bruni, Claudia; Murgia, Alessandra; Cancelli, Alessandro; Turturici, Irene; et al.
Abstract: Background: To evaluate the outcome of patients affected by a single isolated body metastasis treated with stereotactic body radiotherapy (SBRT). Material and methods: Seven-eight patients were treated with SBRT for isolated body metastasis. The most frequent primary tumor was prostate cancer (28.2%), followed by colorectal cancer (23.1%) and lung cancer (20.5%). Median age at diagnosis of oligometastatic disease was 70 years (range 47–88). Median Karnofsky Performance Status (KPS) was 90 (range 70–100). The most common SBRT fractionation scheme was 5 × 7 Gy (total dose 35 Gy). Response to radiotherapy was determined according to RECIST criteria v1.1. Toxicity was registered according to Common Terminology Criteria for Adverse Events (CTCAE) v4.0. The survival analysis was performed with the Kaplan–Meier method. The correlation between time actuarial incidence and clinical parameters was studied, and the Kaplan–Meier method of log-rank test was applied. Results: With a median follow-up of 22.68 months, local control was achieved in 89.7% of the cases. The two-year overall survival (OS) and progression-free survival (PFS) were 68% and 42%, respectively. On univariate analysis, KPS ≥80 is predictive for improved OS ( p = .001) and PFS ( p = .001). Acute toxicity of grade ≥2 occurred in eight (10.2%) patients and late grade ≥2 toxicity in five (6.4%) patients. Conclusions: Ablative radiotherapy in 'early oligometastatic state' is a safe, effective and minimally invasive treatment modality. A good performance status (KPS ≥80) seems to influence the clinical outcome.